Spatial and temporal coverage of the cargo ship network for GNSS-based tsunami detection - Thomas, Bruce E. O.; Foster, James H.; Louartani, Tasnîme (The International Hydrographic Review, 2025)
Tracking changes in sea-surface height with ship-based GNSS can be used to detect tsunamis. One year of navigation data from ships in the Pacific is examined to investigate how well-distributed a cargo-ship network would be for tsunami detection. There is excellent coverage of the most active tsunamigenic zones, with multiple ships predicted within 30-minutes travel time of notable tsunamis. Tsunamigenic regions with low ship density, such as the Southwest Pacific, require a greater percentage of ships participating to ensure sufficient data. The global nature of GNSS and ship routes make this a promising, low-cost approach, to augment tsunami detection.